Some Observations on the Good and Bad Chances of Feasible Social Engineering - Kioukias, Dimitris K. (Advances in Social Sciences Research Journal, 2020)
We attempt to discuss anew the idea of engaging in total social transformation without regard to huge human cost. We argue that “social engineering” entails much more risk than useful achievement, for our destructive capabilities exceed our creativity potential. To support the argument we draw some parallels between key social and political phenomena with aesthetic, communicative, or legal ones. Especially dangerous seems to be a partial appropriation of time, space and history, or a full disregard of them in efforts to change society. In the end we come to the conclusion that, while social manufacturing is feasible, at least to a certain extent, the end result of the process is quite often no better than the previous state of affairs. Therefore, the question of human capacity to effect social transformation should be accompanied by the question “with which specific result”.